Treatment decision making in psychiatry: Formulating patients’ perspectives in outpatient psychiatric consultations - Yao, Xueli; Zhang, Xiaoning (Frontiers in Psychology, 2023)
Seeking and understanding patients’ values and preferences is one of the essential elements in shared decision making, which is associated with treatment adherence in psychiatry. However, negotiating treatment in psychiatric contexts can be challenging with patients whose ability to evaluate treatment recommendations rationally may be impaired. This article attempts to examine a conversational practice that psychiatrists use to deal with patients’ views and perspectives by formulating what the patients have said related to treatment. Taking the naturally occurring, face-to-face outpatient psychiatric consultations as the data, the present study uses conversation analysis (CA) as a method to demonstrate in a fine-grained detail what functions formulations of patients’ perspectives serve in psychiatric contexts. We found that by eliciting patients’ views and perspectives toward treatment, this type of formulation is not only used to achieve mutual understanding and establish the grounds for treatment decisions, but may also be used to challenge the legitimacy of patients’ position, steering treatment decision to the direction preferred by the psychiatrists. We argue that in the process of treatment decision making, psychiatrists do not simply impose their perspectives upon the patients, instead, they attempt to achieve consensus with patients by balancing their institutional authority and orientation to the patients’ perspectives. Data are in Chinese with English translation.